Science Literacy Profile of Junior High School Students on Context, Competencies, and Knowledge - Akhmad Nasor; Achmad Lutfi Lutfi; Binar Kurnia Prahani (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: This study's preliminary goal is to describe junior high school students' proficiency in scientific literacy. It is based on exams that use questions that measure a student's proficiency in scientific literacy, adhering to the guidelines established by the Programme for International Student Assessment (PISA). Method: The research was a quantitative descriptive analysis. It used a list of 20 questions created to evaluate students' proficiency with scientific literacy using a set of predetermined indicators. Purposive sampling was used to gather the data, and 102 students were chosen as a sample from Junior High School 2 Sukorejo. Results: Based on research findings, 19 of the 102 students meet the criteria for scientific literacy skill level 4, the highest level. Additionally, 38 students meet the criteria for level 3 of scientific literacy, which needs to be improved. Furthermore, 45 students continue to meet the low criteria for level 2 scientific literacy skills. According to the findings of this study, future research efforts and increased attention from relevant teachers are required to concentrate more on improving students' scientific literacy skills. Novelty: The novelty of this research explores students' scientific literacy levels using a science literacy test focusing on context, competencies, and knowledge. It provides a comprehensive understanding of students' scientific literacy skills, moving beyond quantitative percentages. The detailed explanation will be valuable for future research and provide deeper insights into the subject matter.